Atrial fibrillation up to 50 days after cardiac surgery should be considered postoperative atrial fibrillation. (25th November 2020) - Van Den Berg, N.W.E; Neefs, J; Kawasaki, M; Jongejan, A; Nariswari, F; Wesselink, R; Van Putte, B.P; Van Boven, W.J; De Jong, J.S.S.G; Hulsman, E.L; Havenaar, H; Klaver, M.N; et al.
Abstract: Introduction: Postoperative atrial fibrillation (POAF) occurs in up to 45% of patients following cardiothoracic surgery and is defined as any atrial tachyarrhythmia occurring ≤30 days after surgery. Consequently, atrial arrhythmias after 30 days are regarded as new-onset AF. However, biological and clinical data on the association between POAF and new-onset AF, or empirical data supporting the cut-off of 30 days, are lacking. Purpose: We hypothesize that patients with POAF are biologically different with respect to atrial fibrosis compared to patients who develop new-onset AF. Methods: PREDICT AF is a prospective, multicenter, observational trial that included patients with a CHA2DS2VAsc score≥2 without a history of AF. Patients underwent CABG or valve surgery and the left atrial appendage (LAA) was removed during surgery. The LAA was obtained for expression analysis of extracellular matrix (ECM) genes such as collagen 1 (COL1A1), collagen 3 (COL3A1) and fibronectin (FN1) by qPCR. Patients were monitored during hospitalisation and followed-up at 1, 6, 12 and 24 months with 24-h Holters and ECGs. The primary endpoint was any recorded atrial tachyarrhythmia lasting >30 seconds. We documented all new-onset arrhythmias over time in order to determine potential cut-offs for POAF (Figure A). We then compared the effects of using a 30-, 50- or 70-day cut-off on the rate of new-onset AF and the differences in expression of fibrosis related genes. Results: PREDICT AF included 150 cardiac surgery patients: 115 CABG, 11 valve surgeries and 24 combined surgeries. Participants had a median follow-up of 1.9 years [1.0–2.0], were 68±7 years old and 19 (13%) were female. POAF <30 days occurred in 63 (42%) patients. New-onset AF >30 days developed in 21 (14%) patients. Of the 21 patients with new-onset AF, 20 (95%) also had had POAF. New-onset AF defined by a cut-off of 50 days, developed in 15 (10%) patients. In total, 9 patients had an episode of AF between 30 and 50 days, of whom 6 (66.6%) had no AF episodes thereafter. Most of these patients under–went (concomitant) aortic valve surgery. The gene expression of ECM components was significantly more predictive of new-onset AF when using a cut-off of 50 days or even 70 days than when using a cut-off of 30 days (Figure B). Conclusion: With stringent monitoring we detected 42% POAF <30 days. One in three POAF patients developed new-onset AF within two years after surgery. However, the majority of the patients who developed new-onset AF between 30 and 50 days postoperatively had no later episodes of AF. Moreover, applying a 50-day cut-off to discriminate POAF from new-onset AF enhanced the prediction of new-onset AF based on the ECM gene expression levels. Our data suggest that both from a biological and a clinical perspective, the cut-off for POAF should be stretched to 50 days postoperatively. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): NWO VIDI